Essays on futures contracts as a feeder cattle price risk management tool - Bina, Justin Dean (Kansas State University, 2020)
This thesis consists of two articles analyzing the feeder cattle futures contract as a price risk management tool. The first article implements transaction-level data and feeder cattle futures interaction terms in a hedonic pricing model framework to estimate optimal feeder cattle hedge ratios conditioned on the price of corn. This deviates from previous feeder cattle hedging literature, which typically employs aggregate weekly data and simple linear regressions of cash price against futures price to estimate hedge ratios. Hedging risk using corn-conditioned hedge ratios is compared to estimated hedge ratios that are not dependent on corn price. The second article again implements transaction-level data and a hedonic pricing model framework to evaluate whether feeder cattle basis risk has changed over time and to identify factors driving basis risk. The method developed in the second article differs from previous livestock basis risk assessments in that out-of-sample transaction price prediction errors are used to represent unexplained cash price deviations from feeder cattle futures price, or basis risk. Results from both articles indicate varying market conditions and animal characteristics have important impacts on the effectiveness of feeder cattle futures for price risk management in a heterogeneous market.
Keywords: Feeder cattle futures; Hedge ratios; Hedging risk; Basis risk; Price risk management